Stainless steel foil with flattening film
Patent Information
- Application Number
- JP2024227562
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-17
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-26
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0015】 粗大な介在物が少ないステンレス鋼箔に平坦化膜を形成して、平坦性および絶縁信頼性を向上した平坦化膜付きステンレス鋼箔を提供することができる。
Smart Images

Figure 2025041831000001 
Figure 2025041831000002 
Figure 2025041831000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a stainless steel foil with a planarizing film that can be used as a flexible substrate for electronic devices. [Background technology]
[0002] Materials for substrates of thin-film electronic devices, such as flexible electronic devices, are required to have flatness, insulation reliability, heat resistance, gas barrier properties, and high toughness. Candidates for substrate materials include resin films and ultra-thin glass, but resin films have problems with heat resistance and gas barrier properties, and ultra-thin glass has low toughness and reliability. On the other hand, stainless steel foils have excellent heat resistance, gas barrier properties, and toughness, but have problems with flatness and insulation. In order to solve the above problems, stainless steel foils with flattening films, which are formed on at least one side of stainless steel foils to impart flatness and insulation, have attracted attention. Among them, stainless steel foils with flattening films coated with silica-based inorganic-organic hybrid materials, which have excellent heat resistance, are promising materials.
[0003] Stainless steel foil on which a film of a silica-based inorganic-organic hybrid material is formed is described in Patent Documents 1 and 2, for example. Patent Document 1 describes a stainless steel foil coated with an inorganic-organic hybrid film that is excellent in heat resistance, workability, flatness, flexibility, and insulation. This stainless steel foil is obtained by coating one or both sides of the stainless steel foil with an inorganic-organic hybrid film containing an appropriate amount of organic groups produced using a sol-gel method, resulting in a stainless steel foil with excellent heat resistance, workability, flatness, insulation, etc.
[0004] Patent Document 2 describes a short-curing flattening film-forming coating liquid capable of flattening the surface of a metal foil coil to the same level as a glass substrate in a roll-to-roll process, a flattening film that is also heat-resistant and moisture-resistant, and a metal foil coil flattened thereby. This metal foil coil is obtained by applying a short-curing flattening film-forming coating liquid obtained by adding 0.1 to 1 mol of acetic acid and 0.005 to 0.05 mol of organotin as catalysts to 1 mol of phenyltrialkoxysilane in an organic solvent, hydrolyzing the mixture with 2 to 4 mol of water, and then distilling off the organic solvent under reduced pressure at a temperature of 160°C to 210°C to obtain a resin, which is then dissolved in an aromatic hydrocarbon solvent.
[0005] On the other hand, even if the above-mentioned planarizing film is provided, there is a problem that the planarizing film cracks due to depressions on the stainless steel foil surface, resulting in a decrease in planarity and insulation. The depressions on the stainless steel foil surface are caused by inclusions in the stainless steel falling off from the stainless steel foil surface during rolling.
[0006] Various methods for reducing inclusions in stainless steel, which is the base material for manufacturing stainless steel foil, have been studied. For example, Patent Document 3 discloses a stainless steel sheet suitable for precision equipment components such as HDD (hard disk drive) components and semiconductor layer formation substrates, including thin-film silicon solar cell substrates. It is disclosed that the presence of minute pits distributed on the surface of the stainless steel sheet has a significant effect on the washability of the stainless steel sheet, and that the minute pits are caused by inclusions, carbide particles, etc. that have fallen off during the rolling process. Patent Document 3 discloses that nonmetallic inclusions mainly composed of Mn(O,S)-SiO2 are generated, and MgO, Al2O3, and Cr2O3 are adjusted to a predetermined concentration or less to render the nonmetallic inclusions harmless. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2003-247078 A [Patent Document 2] International Publication No. 2016 / 076399 [Patent Document 3] JP 2011-202253 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention aims to provide a stainless steel foil with a planarizing film that has excellent flatness and insulation reliability by reducing the number of depressions on the stainless steel foil surface that cause cracks in the planarizing film. [Means for solving the problem]
[0009] The inventors prepared a test piece by forming a planarizing film made of a phenylsiloxane polymer with a thickness of 2.0 μm to 4.0 μm on the surface of a stainless steel foil. 2 More than 9mm 2 The following electrode was used as the upper electrode, the stainless steel foil was used as the lower electrode, and the surface of the test piece was scanned with the upper electrode. When 10 V was applied between the upper electrode and the lower electrode, the leakage current was 1 μA / mm 2 The number of places where the above was true was counted. As a result, the measurement area was 100 cm 2 For 1μA / mm 2 Multiple locations showing current values above this were found. When the cross sections were observed, it was found that there were depressions on the surface of the stainless steel foil with a width of 5 μm or more in the direction perpendicular to the rolling direction, and that these depressions were the cause of crack generation. It was also found that these depressions on the surface of the stainless steel foil were caused by the falling off of coarse inclusions with a grain size of 5 μm or more in the stainless steel during the foil rolling process.
[0010] Further research has revealed that, although it is not possible to track the fallen inclusions, the greater the number of large, unshedded inclusions remaining on the stainless steel foil surface, the greater the number of dents caused by the fallen inclusions and the greater the number of cracks that occur in the planarizing film formed on the stainless steel foil surface.
[0011] Therefore, it was found that the insulation properties and flatness of the stainless steel foil with the planarizing film can be significantly improved by suppressing the coarse inclusions remaining in the stainless steel foil after foil rolling.
[0012] The inventors focused on Al2O3, MgO, SiO2, CaO, Mn(O, S), and CrS as the basic components of inclusions. Among these, inclusions consisting of at least one of SiO2, CaO, Mn(O, S), and CrS are unlikely to form clusters, and are soft with a low melting point. They discovered that coarse inclusions can be reduced by extending or crushing them in the hot rolling or cold rolling process. (SiO2, CaO, Mn(O, S), and CrS are sometimes called soft inclusions.)
[0013] On the other hand, inclusions such as alumina (Al2O3) and magnesium-aluminum spinel (MgO·Al2O3, hereafter sometimes referred to as spinel) have high interfacial energy and are prone to segregation and agglomeration during the solidification process, so they tend to become large in size after agglomeration. Furthermore, because alumina and spinel inclusions are hard, they are difficult to crush during hot rolling or cold rolling, and as a result, they remain as large inclusion particles. (Alumina and magnesium-aluminum spinel are sometimes referred to as hard inclusions.)
[0014] Therefore, the inventors discovered that by reducing the ratio of alumina and spinel contained in the inclusions and reviewing the manufacturing conditions of the stainless steel foil, particularly the rolling conditions, it is possible to reduce the number of coarse alumina and spinel inclusions and finely disperse the soft inclusions, thereby obtaining a stainless steel foil with reduced coarse inclusions. The present invention provides the following: (1) A composition containing a stainless steel component, with the balance being Fe and impurities; With respect to the total mass of inclusions with a grain size of 2.00 μm or more, Al2O3: 30 mass% or less, MgO: 10 mass% or less, Among the inclusions with a diameter of 2.00 μm or more, the number of inclusions with a diameter of more than 5.00 μm present on the surface is 20 / cm 2 is as follows: Stainless steel foil with a thickness of 5.0 μm or more and 100.0 μm or less, and A stainless steel foil with a planarizing film, the stainless steel foil having a planarizing film having a thickness of 0.3 μm or more and 5.0 μm or less on at least one side of the stainless steel foil. (2) The stainless steel foil comprises, in mass%, C: 0.150% or less, Si: 0.100 to 2.000%, Mn: 0.100~10.000% or less, P: 0.045% or less, S: 0.007% or less, Ni: 2.000~15.000%, Cr:15.000~20.000% or less, N: 0.200% or less, Al: 0.030% or less, Mg: 0.0005% or less, The stainless steel foil with a planarizing film according to (1) above, which is an austenitic stainless steel foil containing 0.0005% or less of Ca, with the balance being Fe and impurities. (3) The stainless steel foil comprises, in mass%, C: 0.120% or less, Si: 2.000% or less, Mn: 0.100~1.250% or less, P: 0.040% or less, S: 0.030% or less, Cr:16.000~20.000% or less, N: 0.025% or less, Al: 0.030% or less, Mg: 0.0005% or less, The stainless steel foil with a planarizing film according to (1) above, which is a ferritic stainless steel foil containing 0.0005% or less of Ca, with the remainder being composed of Fe and impurities. (4) A stainless steel foil with a planarizing film according to any one of (1) to (3), wherein the planarizing film is a silica-based organic-inorganic hybrid film, and the Si nuclei constituting the organic-inorganic hybrid film contain only T nuclei and Q nuclei. (5) The stainless steel foil with a planarizing film according to (4) above, wherein the planarizing film is a silica-based organic-inorganic hybrid film, and the ratio of Q nuclei to Si nuclei constituting the organic-inorganic hybrid film is 70% or less. Effect of the Invention
[0015] By forming a planarizing film on stainless steel foil containing few coarse inclusions, it is possible to provide stainless steel foil with a planarizing film having improved flatness and insulation reliability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The stainless steel foil with a planarizing film of the present invention will be described. Unless otherwise specified, "%" for components indicates mass% in the steel. When no lower limit is specified, it may include the case where no component is contained (0%).
[0017] The stainless steel foil according to the present invention is not particularly limited, and may be, for example, an austenitic stainless steel such as SUS304, or a ferritic stainless steel such as SUS430.
[0018] [Stainless steel foil composition] When the stainless steel foil according to the present invention is an austenitic stainless steel foil, the stainless steel foil has a composition, in mass%, containing C: 0.150% or less, Si: 0.050 to 2.000%, Mn: 0.100 to 10.000%, P: 0.045% or less, S: 0.007% or less, Ni: 2.000 to 15.000%, Cr: 15.000 to 20.000%, N: 0.200% or less, Al: 0.030% or less, Mg: 0.0005% or less, Ca: 0.0005% or less, with the balance being Fe and impurities.
[0019] Ni has the effect of improving corrosion resistance and workability, and is also a major component for adjusting the thermal expansion coefficient of stainless steel. From the viewpoint of improving corrosion resistance, the Ni content is 2.000% or more. However, Ni is an expensive element, and if the content is too high, bainite structure is likely to form in the steel after hot rolling or hot forging. Therefore, the Ni content is set to 15.000% or less.
[0020] Cr is an alloying component necessary for improving corrosion resistance, but if an excessive amount of Cr is contained, the steel material becomes hard and its workability deteriorates, so the Cr content is 20.000% or less. There is no particular lower limit for the Cr content, but the effect of adding Cr becomes significant at a content of 15.000% or more, so the lower limit is 15.000% or more.
[0021] C (carbon) may not be contained. If C is contained in excess, the thermal expansion coefficient increases, and the amount of Cr-based inclusions precipitated at the grain boundaries increases, causing the generation of large inclusion particles. Therefore, the C content is 0.150% or less, preferably 0.100% or less, and more preferably 0.050% or less.
[0022] Ca dissolves in sulfides, finely disperses the sulfides, and makes the sulfides spherical. On the other hand, if a large amount of Ca is contained, the Ca that is not dissolved in the sulfides may form coarse oxides, which may cause etching defects. Therefore, it is not necessary to contain Ca, but if it is contained, the Ca content is 0.0005% or less, preferably 0.0001% or less.
[0023] Mn is actively used as a deoxidizer instead of Mg and Al to avoid the formation of spinel. However, if the Mn content is too high, it segregates at the grain boundaries, promoting grain boundary fracture, and the hydrogen embrittlement resistance is rather reduced. Therefore, the Mn content is 10.000% or less, preferably 5.000% or less, 2.000% or less, 1.500% or less, 1.200% or less, 1.000% or less, and more preferably 0.800% or less, 0.600% or less, 0.500% or less. There is no particular lower limit for Mn. However, if the Mn content is too low, it becomes difficult to adjust the inclusions to a Mn(O,S)-SiO2-based composition. Therefore, Mn is 0.100% or more. Here, Mn(O,S) refers to simple MnO, simple MnS, and inclusions of a combination of MnO and MnS. The ratio of O and S is not constant, and Mn(O,S) refers to inclusions of a combination of oxides and sulfides.
[0024] In order to avoid the formation of spinel, deoxidation with Mn and Si is actively performed instead of deoxidation with Mg and Al. However, Si increases the thermal expansion coefficient of stainless steel. In addition, the deoxidation product MnO-SiO2 is a vitrified soft inclusion, which is elongated and divided during hot rolling to be refined. Therefore, hydrogen embrittlement resistance is improved. On the other hand, if the Si content exceeds 2.000%, the strength becomes too high and the steel becomes hard, and many passes are required to roll the steel to a predetermined thickness when manufacturing a thin plate by cold working, and productivity is greatly reduced. Therefore, Si is 2.000% or less, preferably 1.000% or less, 0.500% or less, and more preferably 0.300% or less. There is no particular limit on the lower limit of Si, but if it is too small, deoxidation is insufficient, the Cr2O3 concentration in the inclusions increases, and inclusions that induce processing cracks are easily formed. Therefore, the lower limit of Si is 0.050%, preferably 0.100%.
[0025] Mg is used to deoxidize steel. However, if the Mg content exceeds 0.0005%, coarse inclusions may form. Also, to avoid the formation of spinel, it is preferable that the Mg content is low. Therefore, the Mg content is 0.0005% or less, preferably 0.0003% or less, 0.0002% or less, and more preferably 0.0001% or less.
[0026] Al is also used to deoxidize steel. However, if the Al content exceeds 0.030%, coarse inclusions may be generated, causing poor etching. In addition, it is preferable that the Al content is low in order to avoid the generation of spinel. Therefore, the Al content is 0.030% or less, preferably 0.020% or less, 0.010% or less, and more preferably 0.005% or less.
[0027] Since P and S are elements that combine with alloy elements such as Mn in iron-based alloys to form inclusions, the lower the content, the better. Therefore, the P content is 0.045% or less, preferably 0.010% or less, 0.007% or less, and more preferably 0.005% or less. The S content is 0.007% or less, and more preferably 0.005% or less.
[0028] N, like C, is a solid solution strengthening element. When contained in large amounts, it increases the 0.2% yield strength and hardens the steel. On the other hand, when contained in large amounts, it significantly deteriorates manufacturability, so the upper limit of N content is 0.200%.
[0029] The balance of the above steel components is Fe and inevitable impurities. The inevitable impurities herein refer to components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, during industrial production of steel, and are permissible within a range that does not adversely affect the present invention.
[0030] When the stainless steel foil according to the present invention is a ferritic stainless steel foil, the stainless steel foil has a composition, in mass%, containing C: 0.120% or less, Si: 0.050 to 2.000%, Mn: 0.100 to 1.250%, P: 0.040% or less, S: 0.030% or less, Cr: 15.000 to 20.000%, N: 0.025% or less, Al: 0.030% or less, Mg: 0.0005% or less, Ca: 0.0005% or less, with the balance being Fe and impurities.
[0031] Cr is an alloying element necessary for improving corrosion resistance. However, if an excessive amount of Cr is included, the steel material becomes hard and its workability deteriorates, so the Cr content is 20.000% or less. There is no particular lower limit for the Cr content, but the effect of adding Cr becomes significant at a content of 15.000% or more, so the lower limit is 15.000% or more.
[0032] C (carbon) may not be contained. If C is contained in excess, the thermal expansion coefficient increases, and the amount of Cr-based inclusions precipitated at the grain boundaries increases, causing the generation of large inclusion particles. Therefore, the C content is 0.120% or less, preferably 0.100% or less, and more preferably 0.050% or less.
[0033] Ca dissolves in sulfides, finely disperses the sulfides, and makes the sulfides spherical. On the other hand, if a large amount of Ca is contained, the Ca that is not dissolved in the sulfides may form coarse oxides, which may cause etching defects. Therefore, it is not necessary to contain Ca, but if it is contained, the Ca content is 0.0005% or less, preferably 0.0001% or less.
[0034] Mn is actively used as a deoxidizer instead of Mg and Al to avoid the formation of spinel. However, if the Mn content is too high, it segregates at the grain boundaries, promoting grain boundary fracture, and the hydrogen embrittlement resistance is rather reduced. Therefore, the Mn content is 1.250% or less. It is preferably 0.800% or less, 0.600% or less, and more preferably 0.500% or less. However, if the Mn content is too low, it becomes difficult to adjust the inclusions to a Mn(O,S)-SiO2 composition. Therefore, Mn is 0.100% or more. Here, Mn(O,S) refers to MnO alone, MnS alone, and inclusions in which MnO and MnS are combined, and the ratio of O and S is not constant, and refers to inclusions in which oxides and sulfides are combined.
[0035] In order to avoid the formation of spinel, deoxidation with Mn and Si is actively performed instead of deoxidation with Mg and Al. However, Si increases the thermal expansion coefficient of stainless steel. In addition, the deoxidation product MnO-SiO2 is a vitrified soft inclusion, which is elongated and divided during hot rolling to be refined. Therefore, hydrogen embrittlement resistance is improved. On the other hand, if the Si content exceeds 2.000%, the strength becomes too high and the steel becomes hard, and many passes are required to roll the steel to a predetermined thickness when manufacturing a thin plate by cold working, and productivity is greatly reduced. Therefore, Si is 2.000% or less, more preferably 1.000% or less, 0.500% or less, and more preferably 0.300% or less. There is no particular limit on the lower limit of Si, but if it is too small, deoxidation is insufficient, the Cr2O3 concentration in the inclusions increases, and inclusions that induce processing cracks are easily formed. Therefore, the lower limit of Si is 0.050%, preferably 0.100%.
[0036] Mg is used to deoxidize steel. However, if the Mg content exceeds 0.0005%, coarse inclusions may form. Also, to avoid the formation of spinel, it is preferable that the Mg content is low. Therefore, the Mg content is 0.0005% or less, preferably 0.0003% or less, 0.0002% or less, and more preferably 0.0001% or less.
[0037] Al is also used to deoxidize steel. However, if the Al content exceeds 0.030%, coarse inclusions may be generated, causing poor etching. In addition, it is preferable that the Al content is low in order to avoid the generation of spinel. Therefore, the Al content is 0.030% or less, preferably 0.020% or less, 0.010% or less, and more preferably 0.005% or less.
[0038] Since P and S are elements that combine with alloy elements such as Mn in iron-based alloys to form inclusions, the lower the content, the better. Therefore, the P content is 0.040% or less, preferably 0.010% or less, 0.007% or less, and more preferably 0.005% or less. The S content is 0.030% or less, preferably 0.010% or less, 0.007% or less, and more preferably 0.005% or less.
[0039] N, like C, is a solid solution strengthening element. When contained in large amounts, it increases the 0.2% yield strength and hardens the steel. On the other hand, when contained in large amounts, it significantly deteriorates manufacturability, so the upper limit of N content is 0.025%.
[0040] The balance of the above steel components is Fe and impurities. Here, the term "impurities" refers to components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, during industrial production of steel, and are permissible within a range that does not adversely affect the present invention.
[0041] [Inclusions] Fewer inclusions are better, and ideally there should be no inclusions at all, but it is not easy to completely eliminate them, as they are mixed in during the manufacturing process or are generated from the steel components. As mentioned above, it has been found that large inclusions on the surface tend to fall off during rolling and become the cause of dents. Therefore, it is important to reduce inclusions with a large diameter of 5 μm or more in equivalent circle diameter as much as possible.
[0042] The inventors focused on Al2O3, MgO, SiO2, CaO, Mn(O,S), and CrS as basic components of inclusions. Among these, it was found that soft inclusions such as SiO2, CaO, Mn(O,S), and CrS are difficult to cluster, have a low melting point, and are soft, so they are elongated or crushed by rolling, and coarsening is suppressed. On the other hand, hard inclusions such as alumina and magnesium-aluminum spinel have high interfacial energy and are prone to segregation and aggregation during the solidification process, so that the size after aggregation tends to be large. Furthermore, it was also found that alumina and spinel inclusions are difficult to elongate or crush during rolling because they are hard, and as a result, they remain as inclusion particles with large sizes.
[0043] Based on these findings, it was considered that while suppressing the generation of soft inclusions themselves, it is important to refine any soft inclusions that are generated by adjusting the rolling conditions (e.g., reduction ratio), and on the other hand, because it is difficult to refine hard inclusions by rolling, it is important not to generate or mix in hard inclusions, and even if they are generated or mixed in, it is important not to allow them to aggregate (to coarsen).
[0044] First, in both the soft and hard types, in order to ensure the mechanical strength of the stainless steel foil without generating inclusions, it is advisable to use the steel composition as described above. It is important to review the process to prevent inclusions from being mixed in. For example, it is advisable to review the refractories used in molten metal treatment and use refractories with low amounts of Al and Mg. Furthermore, one of the causes of the aggregation of inclusions is, for example, segregation and aggregation when solidifying from the molten metal. Although it is not easy to prevent segregation during solidification, methods such as stirring the molten metal to prevent aggregation as much as possible can be considered. Furthermore, it is advisable to manufacture ingots using a process that does not use the solidification process from the molten metal, such as HIP (hot isostatic pressing). The manufacturing process will be explained later.
[0045] For measurement reasons, the inclusions contained in the stainless steel foil of the present invention are inclusions with a particle size (equivalent circle diameter) of 2.00 μm or more (hereinafter, unless otherwise specified, may be simply referred to as "inclusions"). Since coarse inclusions with a particle size of more than 5.00 μm are harmful and should be reduced as much as possible, inclusions with a particle size of 2.00 to 5.00 μm are preferably reduced, but are not directly harmful.
[0046] In addition, since hard inclusions such as alumina and spinel tend to become coarse, it is advisable to reduce them as much as possible. Therefore, Al2O3 is 30 mass% or less and MgO is 10 mass% or less with respect to the total mass of inclusions with a particle size of 2.00 μm or more. Since it is preferable that these hard inclusions are small, the ratio of Al2O3 is preferably 25 mass% or less, 20 mass% or less, 15 mass% or less, 10 mass% or less, and more preferably 5 mass% or less, 3 mass% or less, 1 mass% or less. The ratio of MgO is preferably 8 mass% or less, 6 mass% or less, 5 mass% or less, and more preferably 4 mass% or less, 3 mass% or less, 2 mass% or less, 1 mass% or less.
[0047] Furthermore, the stainless steel foil according to the present invention has a surface area of inclusions with a circular equivalent diameter of more than 5.00 μm of 20 pieces / cm 2 The present invention is characterized in that:
[0048] According to the present invention, the number ratio of inclusions having a particle size of more than 5.00 μm contained in the stainless steel foil to which the flattening film is applied is set to 20 pieces / cm on the stainless steel foil surface. 2 It is necessary to limit the thickness to the following. Depressions on the stainless steel foil surface are the cause of cracks in the flattened film. During rolling after the sheet thickness is thinned to a certain extent and the inclusions are refined to a certain degree, inclusions with a particle size of 5.00 μm or more on the stainless steel foil surface fall off from the stainless steel foil surface, causing these depressions.
[0049] The particle size of the inclusions was measured as follows. The inclusions on the surface of the stainless steel foil were observed using a scanning electron microscope (SEM). As the SEM, for example, JSM-IT500HR manufactured by JEOL Ltd. may be used. An example of the SEM settings is shown below. Detector: Backscattered electron detector BED-C Magnification: 80x Acceleration voltage: 20.0 kV Working Distance (WD): 10.0mm ·Irradiation current: 80% In addition, inclusions were detected from the images acquired by the SEM using automatic inclusion analysis software, and the composition of the inclusions was analyzed using an energy dispersive X-ray spectrometer (hereinafter referred to as an EDS device). For the automatic inclusion analysis software, for example, the particle analysis mode of AZtec manufactured by Oxford Co., Ltd. may be used. For the EDS device, for example, ULTIM MAX 65 manufactured by Oxford Co., Ltd. may be used. In the process of identifying inclusions using the automatic inclusion analysis software, first an SEM image is acquired to be used in the automatic inclusion analysis software. Next, from the image acquired by SEM, the automatic inclusion analysis software identifies an inclusion as an inclusion if the equivalent circle diameter is 2.00 μm or more and one or more of the elements Al, Mg, Si, Ca, Mn, or S are detected by EDS. Images that have been subjected to EDS analysis are combined in the software and output as a single image. At that time, the equivalent circle diameter and elemental composition of the inclusion identified by the automatic inclusion analysis software are also acquired. The above steps for identifying inclusions are repeated to measure up to the set area. For example, if the measurement area of the image is 10 cm, 2 The unit of measurement was one visual field, and 10 visual field measurements were performed for a total of 100 cm 2 The diameter of a circle having the same area as the area of the measured inclusion is taken as the equivalent circle diameter, and this is taken as the "grain size." As described above, the surface of the stainless steel foil was observed to determine the particle size of the inclusions, but it is clear that there is no particular difference between the particle size of the inclusions present on the surface of the stainless steel foil and the particle size of the inclusions present in the stainless steel foil.
[0050] The composition of inclusions is calculated as follows for each inclusion identified by the automatic inclusion analysis software. First, the mass percentages of the elements Al, Mg, Si, Ca, Mn, Cr, and S obtained by EDS analysis are divided by their atomic weights to determine the apparent amount of substance of the elements. Next, the above seven elements are converted into oxides or sulfides, which are the basic components of inclusions. In inclusions, Al, Mg, Si, and Ca exist mainly as oxides. Mn and Cr exist mainly as sulfides, and Mn can also exist as the oxide MnO. In addition to the sulfide MnS mentioned above, S can also exist as chromium sulfide CrS. When the apparent amount of substance of S is greater than the apparent amount of substance of Mn, there is an amount of MnS equal to the apparent amount of substance of Mn, and in this case, there is an amount of CrS equal to the apparent amount of substance of Mn minus the apparent amount of substance of S. When the apparent amount of substance of S is less than the apparent amount of substance of Mn, there is an amount of MnS equal to the apparent amount of substance of S, and in this case, there is an amount of MnO equal to the apparent amount of substance of Mn minus the apparent amount of substance of S. When the apparent amount of substance of Mn and the apparent amount of substance of S are exactly the same, there are an amount of MnS equal to the amounts of substance of Mn and S. In order to make the inclusions into oxides or sulfides, which are the basic components, the substance amounts of the elements O (oxygen) or S corresponding to the apparent substance amounts of the elements are given based on the theoretical ratios of Al:O=2:3, Mg:O=1:1, Si:O=1:2, Ca:O=1:1, Mn:O=1:1, Mn:S=1:1, and S:Cr=1:1, respectively, and then multiplied by the molecular weight of each element to derive the oxide, etc. equivalent mass. Each of the oxide, etc. equivalent masses thus obtained is divided by the total of the seven oxide, etc. equivalent masses to obtain the oxide, etc. equivalent mass% of Al2O3, MgO, SiO2, CaO, MnO, MnS, and CrS (hereinafter sometimes referred to as "oxides, etc."). The seven oxide, etc. equivalent mass% are multiplied by the area of the inclusions obtained by the automatic inclusion analysis software to obtain the inclusion area (μm 2 ) is required. Next, the inclusion area is calculated for each of the inclusions identified by the automatic inclusion analysis software, and the inclusion areas for each of the seven oxides or sulfides are summed up to obtain the total area of Al2O3, the total area of MgO, the total area of SiO2, the total area of CaO, the total area of MnO, the total area of MnS, and the total area of CrS. The sum of these seven total areas is regarded as the total area of all inclusions. The composition ratio (mass%) of the inclusions is calculated by dividing the total area of each oxide, etc. by the total area of all inclusions.
[0051] The number density of inclusions with a grain size of more than 5.00 μm is set to 20 pieces / cm 2 This reduces the number of inclusions that are large enough to cause dents on the surface of the stainless steel foil, which can lead to cracks in the flattening film. The fewer inclusions with a particle size of more than 5.00 μm, the better, and the lower the density is preferably 15 pieces / cm. 2 Below, 12 pieces / cm 2 Below, 10 pieces / cm 2 More preferably, 8 particles / cm or less. 2 Below, 6 pieces / cm 2 Below, 5 pieces / cm 2 The following is the result.
[0052] Plate Thickness The stainless steel foil used in the present invention has a thickness of 5.0 μm or more and 100.0 μm or less. If the thickness is greater than 100.0 μm, the foil will not have the desired flexibility and will lose the advantage of being lightweight, which is a major feature of the foil. A stainless steel foil having a thickness of less than 5.0 μm is very susceptible to folding or wrinkling during handling, making it difficult to adapt to industrial processes, and its strength as a substrate is reduced, causing reliability problems during use. Furthermore, such a thin stainless steel foil is inevitably expensive from an industrial point of view. The thickness of the stainless steel foil used in the present invention can be measured using a so-called contact type micrometer. It is more preferable that the thickness of the stainless steel foil used in the present invention is 10.0 μm or more and 80.0 μm or less in order to prevent cracks from occurring in the flattening film.
[0053] The method for producing the planarizing film-coated stainless steel foil of the present invention will now be described. The stainless steel foil according to the present invention can be produced, for example, as follows, however, the method described below is merely an example and is not intended to be limiting.
[0054] For example, 10 -1 In a vacuum atmosphere of 1000 Torr or less, raw materials adjusted to a specified composition are vacuum melted to obtain a molten metal with the desired alloy composition. At this time, in order to deoxidize the molten metal, Mn and Si are added so that the Mn and Si contents of the molten metal after slag removal are the specified contents, respectively.
[0055] Next, atomization (pulverization) is performed by gas atomization using an inert gas such as Ar or N2 gas. The molten metal temperature during gas atomization is preferably in the range of melting point + 50°C to 200°C in order to reduce the viscosity of the molten metal. The gas flow rate (m 3 / min) / molten metal flow rate (kg / min) ratio is 0.3 (m 3 / kg) or more. 3 / min) / molten metal flow rate (kg / min) ratio is 0.3 (m 3 If the melt cooling rate is less than 1 / kg, the cooling rate of the droplets will be too slow, and the liquid phase ratio of the droplets when they collide with the ingot surface will be too high, causing the inclusions to become coarse. Therefore, the ratio of gas flow rate to molten metal flow rate is 0.3 (m 3 / kg) or more, preferably 0.5 or more, 0.7 or more, 0.9 or more, 1.0 or more, 1.5 or more, and more preferably 2.0 or more. 3 The upper limit of the ratio of the flow rate of the melt (kg / min) to the flow rate of the molten metal (kg / min) is not particularly limited, but is preferably 5.0 (m 3 Above this, the cooling capacity is saturated, so the upper limit is 5.0 (m 3 / kg).
[0056] The alloy powder obtained by the atomization process is sintered by hot pressing or HIP to produce an ingot. The sintering method is not particularly limited. The conditions may be set appropriately according to a conventional hot pressing method.
[0057] The smaller the grain size of the alloy powder, the easier it is to sinter, but the productivity is lower than that of alloy powder with a larger grain size. On the other hand, the larger the grain size of the alloy powder, the easier it is to mix impurities from the furnace material. Therefore, the grain size of the alloy powder is set to 300 μm or less, preferably 250 μm or less, 200 μm or less, 150 μm or less, and more preferably 100 μm or less.
[0058] The atomization (pulverization) method described above can suppress the content of Al and Mg, and the sintering method, which processes in the solid phase, also suppresses the generation of coarse inclusions (e.g., 5 μm or larger) because there is no contamination of Al or Mg from the refractory material as occurs with the solidification method (casting method). As a result, the amount of Al2O3 and spinel-based inclusions themselves is ultimately reduced, and the generation of coarse inclusions, particularly 5 μm or larger, can be significantly suppressed.
[0059] Next, the produced alloy ingot is subjected to hot forging, cutting, or grinding to produce a steel billet, and the steel billet is rolled to a thickness of 3.0 mm to 200 mm. The rolling may be hot rolling or cold rolling. The rolled plate having a thickness of 3.0 mm to 200 mm is formed into a stainless steel foil having a thickness of 100.0 μm or less by repeatedly carrying out the rolling process. The lower limit of the plate thickness is 5.0 μm to obtain the effects of the present invention.
[0060] An annealing step may be performed before or after hot rolling, hot forging, or cold rolling the ingot. The temperatures in the annealing, hot forging, and hot rolling steps are lower than the melting point of the iron-based alloy of the present invention in order to prevent aggregation of inclusions, and are preferably in the range of the melting point of the iron-based alloy of the present invention minus 500°C or more and the melting point of the iron-based alloy of the present invention minus 200°C or less.
[0061] After hot rolling or hot forging, cold rolling may be performed. Intermediate annealing may be performed during cold rolling. Rolling can elongate and crush inclusions, particularly soft inclusions, and refine the inclusions. Cold rolling is more effective than hot rolling in refining inclusions, and the thinner the plate thickness, the more effective it is. Therefore, the total reduction rate of cold rolling should be 96.0% or more based on the plate thickness after hot rolling (plate thickness immediately before cold rolling). It is preferably 97.0% or more, 98.0% or more, 99.0% or more, or 99.5% or more. Furthermore, since a higher reduction rate is expected to have a greater effect of refining inclusions, the reduction rate in each pass should be 20.0% or more, except for the pass for making the plate into the target thickness and the pass for correcting the shape. By cold rolling at such a reduction rate, soft inclusions can be refined by elongation and crushing, and dispersed.
[0062] On the other hand, in the rolling (finish rolling) after the plate thickness is thinned to a certain extent and the inclusions are refined to a certain extent, it has been found that the inclusions are refined and at the same time, surface irregularities are generated due to the inclusions falling off, and pinholes that penetrate the stainless steel foil are generated. Therefore, in the finish rolling (multi-stage rolling) from a plate thickness 10 to 80 μm thicker than the final plate thickness to the final plate thickness, it is recommended to perform mild rolling by controlling the unit rolling load (kN / mm) of each pass to an appropriate range. The unit rolling load is the load applied to the workpiece from the rolling roll divided by the plate width of the workpiece. For example, the unit rolling load should be 0.4 to 1.3 kN / mm, and the cumulative rolling reduction should be 50.0% or more. If the unit rolling load is less than 0.4 kN / mm, the processing heat generated during rolling is small and the flexibility of the alloy foil, which is the workpiece, is reduced, so that cracks occur at the interface between the inclusions and the alloy foil, and the inclusions fall off more frequently. Moreover, when it exceeds 1.3 kN / mm, the processing heat increases, but the amount of plastic deformation of the alloy foil itself increases, so that cracks occur at the interface with the inclusions, and the inclusions fall off more frequently. Furthermore, when the cumulative reduction rate of the finish rolling is less than 50.0%, the strength of the alloy foil may not be fully developed. The upper limit of the cumulative reduction rate of the finish rolling is not particularly limited, but it is preferable to set it to 98.0% or less based on the capacity of a normal foil rolling machine.
[0063] Furthermore, in order to prevent the generation of surface irregularities due to the falling off of inclusions, the reduction in the final rolling to the final plate thickness should be 0.2 to 3.0%. Here, the reduction is expressed by the following formula, where t1 is the plate thickness before rolling and t2 is the plate thickness after rolling. Reduction rate=(t1-t2) / t1 For example, the cumulative reduction ratio of the finish rolling may be multi-stage, where the thickness before the finish rolling is t1 and the thickness after the finish rolling is t2. The reduction ratio of each pass may be t1 before each rolling pass and t2 after the rolling pass.
[0064] Furthermore, after the finish rolling (final rolling), annealing may be performed to remove distortion.
[0065] [Planarization film composition] The planarizing film used in the production of the planarizing film-coated stainless steel foil of the present invention is a silica-based inorganic-organic hybrid film. [Silica-based inorganic-organic hybrid film] Silica-based inorganic-organic hybrid films generally have a structure containing R2Si(OR')2, RSi(OR')3, or Si(OR')4 as the basic unit of silicone, and are obtained by applying a coating liquid that has been hydrolyzed and condensed in a solvent and then heat treating it. Here, R is any organic group, and R' is an alkyl group. R2Si(OR')2, RSi(OR')3, and Si(OR')4 correspond to the D nucleus (bifunctional), T nucleus (trifunctional), and Q nucleus (tetrafunctional) of Si, respectively.
[0066] When the silica-based inorganic-organic hybrid film constituting the planarization film contains a D nucleus of Si as a component, it can impart flexibility to the film, but during the high-temperature process of device fabrication, the D nucleus forms a three-membered ring and is removed, which adversely affects the characteristics of the device. For this reason, it is required that the Si nucleus constituting the planarization film is a silica-based inorganic-organic hybrid film composed only of T nucleus and Q nucleus. If the ratio of Q nucleus to the total Si nucleus is more than 70%, the density of the Si-O bonds constituting the film becomes too high, and in this case, it is unsuitable because the film is prone to cracks. Since the T nucleus has one organic group directly bonded to Si, it can impart flexibility to the film. It is preferable that the ratio of Q nucleus is 70% or less.
[0067] The organic group R directly bonded to the Si constituting the silica-based inorganic-organic hybrid film according to the present invention is not particularly limited. For example, a methyl group or a phenyl group is preferable from the viewpoint of heat resistance. The methyl group and the phenyl group may be contained alone or both may be contained simultaneously. The type and amount of the Si nucleus in the planarization film can be identified by 29Si-NMR measurement. The organic group directly bonded to Si can be examined by FTIR or a combination of 13C-NMR and 1H-NMR.
[0068] [Silica-based inorganic-organic hybrid film forming coating solution] The silica-based inorganic-organic hybrid film can be prepared by various methods. When the silica-based inorganic-organic hybrid film is a phenyl group-modified silica film, it is prepared, for example, from the coating liquid shown below. The following methods are merely examples and are not intended to be limiting.
[0069] This coating liquid is prepared by adding 0.1 to 1 mol of acetic acid and 0.005 to 0.050 mol of organotin as catalysts to 1 mol of phenyltrialkoxysilane in an organic solvent, hydrolyzing the phenyltrialkoxysilane with 2.0 to 4.0 mol of water, and then distilling off the organic solvent used in the hydrolysis of the phenyltrialkoxysilane, as well as water and alcohol as reaction by-products, under reduced pressure at a temperature of 160°C to 210°C, to obtain a resin, which is then dissolved in an aromatic hydrocarbon solvent.
[0070] Examples of the phenyltrialkoxysilane used herein include phenyltrimethoxysilane, phenyltriethoxysilane, and phenyltripoxysilane.
[0071] Examples of organic solvents that can be used when hydrolyzing phenyltrialkoxysilane include methanol, ethanol, and propanol.
[0072] The organic solvent distilled off during vacuum distillation includes the organic solvent used to hydrolyze the phenyltrialkoxysilane, as well as alcohol produced by hydrolysis of the phenyltrialkoxysilane, and may also include water produced in the condensation reaction of the hydrolyzed phenyltrialkoxysilane.
[0073] Examples of aromatic hydrocarbon solvents include toluene, xylene, etc. Other organic solvents may be mixed with the aromatic hydrocarbon solvents as long as the mixture does not affect the properties.
[0074] Organotin is a catalyst that promotes the polycondensation reaction of phenyltrialkoxysilane and its hydrolysis condensation reaction product, and phenyl group-containing ladder polymer. Organotin includes dibutyltin diacetate, bis(acetoxydibutyltin) oxide, dibutyltin bisacetylacetonate, dibutyltin bismaleic acid monobutyl ester, dioctyltin bismaleic acid monobutyl ester, bis(lauroxydibutyltin) oxide, etc.
[0075] The silica-based inorganic-organic hybrid film is formed by applying the above-mentioned coating liquid to the surface of a stainless steel foil and curing it at a heat treatment temperature of 300°C or more and 450°C or less in an inert gas atmosphere, preferably to a film thickness of 0.3 μm or more and 5.0 μm or less.
[0076] When the silica-based inorganic-organic hybrid film is a methyl group-modified silica film, it is prepared from, for example, the coating liquid shown below. 0.6 mol of methyltriethoxysilane and 0.4 mol of tetramethoxysilane are hydrolyzed and condensed with 2.0 mol of water and 0.1 mol of acetic acid in 12.0 mol of ethanol, and the coating solution is applied to a thickness of 1.0 μm, and then heat-treated in nitrogen at 450°C for 10 minutes to produce a film with 60% T nuclei with methyl groups bonded and 40% Q nuclei. In addition to tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, colloidal silica, etc. can be used as the raw material for the Q nuclei. In addition to methyltriethoxysilane, methyltrimethoxysilane can also be used. These raw materials may be combined in combination.
[0077] In the silica-based inorganic-organic hybrid film, the organic group of the raw material organoalkoxysilane may be thermally decomposed and Si may change from T nucleus to Q nucleus depending on the heat treatment temperature after coating and the gas atmosphere during the heat treatment. Therefore, when a coating liquid obtained by hydrolyzing and condensing a raw material that is a T nucleus, for example 1.0 mol of methyltrimethoxysilane, in 8.0 mol of methanol with 3.0 mol of water and 0.01 mol of nitric acid is applied to a thickness of 0.4 μm and then heat-treated at 500 ° C for 1 minute in nitrogen containing 0.1% oxygen, 98% of the Si in the T nucleus bound to the methyl group and 2% of the Si in the Q nucleus resulting from the thermal decomposition of the methyl group are present in the planarized film. On the other hand, when the coating liquid is applied to a stainless steel foil with a thickness of 0.4 μm and then heat-treated at 500 ° C for 1 minute in nitrogen, the Si in the T nucleus bound to the methyl group becomes 100%.
[0078] The thickness of the silica-based inorganic-organic hybrid film formed on the stainless steel foil is 0.3 μm or more and 5.0 μm or less. If it is thinner than 0.3 μm, the coverage of the stainless steel foil surface will be insufficient, causing a short circuit between the stainless steel foil and the device, or the surface of the silica-based inorganic-organic hybrid film will not be sufficiently flat, causing delamination of the electrode layer and semiconductor layer that constitute the device, which is unsuitable. If it exceeds 5.0 μm, the film will be prone to cracking. Not only will cracks easily occur during film formation, but the stainless steel foil covered with the flattening film will also be prone to cracking when bent as a flexible substrate. It is even more preferable that the film thickness be 0.5 μm or more and 3.5 μm or less from the viewpoints of coverage of the stainless steel foil surface and prevention of cracks. EXAMPLES
[0079] The present invention will now be further described with reference to examples, although it should be understood that the present invention is not limited to the examples presented herein.
[0080] For test materials 1 and 2, molten metal of stainless steel alloy composition adjusted to the components shown in Table 1 was prepared in a vacuum induction melting furnace, and powdered by gas atomization with N2 gas. The molten metal temperature during gas atomization was set in the range of liquidus temperature + 50°C to liquidus temperature + 200°C in order to reduce the viscosity of the molten metal. The gas flow rate (m 3 / min) / molten metal flow rate (kg / min) ratio is 1.0 to 3.0 (m 3 / kg). Next, the obtained alloy powder was sealed in a metal container, and ingots of test materials 1 and 2 were produced by a known HIP treatment method.
[0081] For test materials 3 and 4, molten metal with the stainless steel alloy composition shown in Table 1 was prepared in a vacuum induction melting furnace, and then the molten metal was transferred to a mold and solidified in the mold to produce an ingot. During this process, the refractories for the tundish containing the molten metal and the inner wall of the mold were the same as those used in normal operations.
[0082] A part of the test materials 1 and 2 and each ingot of the test materials 3 and 4 were hot forged to produce a steel piece with a cross section of 80 mm x 80 mm, and the steel piece was hot rolled to a thickness of 3.0 mm, and then cold rolled to obtain a steel plate with a thickness of 0.30 mm. The obtained steel plate was cold rolled to obtain a rolling reduction of 20.0% or more in each pass, except for the pass for making the target plate thickness and the pass for correcting the shape, to obtain a steel foil with a thickness 50 μm thicker than the final plate thickness. The steel foil obtained from the test materials 1 and 2 was finish rolled to produce stainless steel foils with thicknesses of 5.0 μm, 10.0 μm, 25.0 μm, 50.0 μm, and 100.0 μm. The steel foil obtained from the test materials 3 and 4 was finish rolled to produce a stainless steel foil with a thickness of 50.0 μm. At this time, the unit rolling load was set to 0.4 to 1.3 kN / mm, and the reduction ratio of the final finish rolling was set to 0.2 to 3.0%. Note that tension annealing was performed to remove distortion caused by cold rolling. The stainless steel foils produced from test material 1 were named test materials 1-1, 1-2, 1-3, 1-4, and 1-5, in the order of thickness 5.0 μm, 10.0 μm, 25.0 μm, 50.0 μm, and 100.0 μm. The stainless steel foils produced from test material 2 were similarly named test materials 2-1, 2-2, 2-3, 2-4, and 2-5. The stainless steel foil produced from test material 3 was named test material 3-1, and the stainless steel foil produced from test material 4 was named test material 4-1.
[0083] A part of each ingot of test materials 1 and 2 was hot forged to produce a steel piece with a cross section of 80 mm x 80 mm, and the steel piece was hot rolled to a thickness of 3.0 mm, and then cold rolled to obtain a steel plate with a thickness of 0.30 mm. The obtained steel plate was cold rolled, and the reduction rate in each pass was less than 20.0%, except for the pass for making the target thickness and the pass for shape correction, to obtain a steel foil with a thickness of 50.0 μm thicker than the final thickness. The obtained steel foil was finish rolled to produce a stainless steel foil with a thickness of 50.0 μm. At this time, the reduction rate of the final finish rolling was 5.0%. In addition, tension annealing was performed to remove distortion due to cold rolling. The stainless steel foil produced from test material 1 was named test material 1-6, and the stainless steel foil produced from test material 2 was named test material 2-6.
[0084] [Table 1]
[0085] A coating solution for forming a phenyl group-containing silica-based inorganic-organic hybrid film was prepared. First, using a 1L flask, the raw materials were mixed to have the compounding ratio shown in Table 2, and the total amount was 0.7L. After mixing, the raw materials were stirred and mixed with a magnetic stirrer for 15 minutes, and refluxed under nitrogen gas flow at 80 ° C for 3 hours to promote hydrolysis. Then, using a rotary evaporator, the set temperature of the oil bath was set to 80 ° C, the solvent was distilled under reduced pressure, and a condensation reaction product was obtained. Then, toluene was added in an amount equal to the weight of the condensation reaction product to dissolve the condensation reaction product. This 1L flask was connected to a reflux condenser with a Dean-Stark trap, and heating was performed under reflux. The set temperature of the oil bath and the reflux time during heating and reflux are shown in Table 2. After heating and refluxing, toluene was further added to dilute the solid concentration to 30 mass%, and a filter with a pore size of 5 μm was set to perform vacuum filtration to obtain a coating solution for forming a phenyl group-containing silica-based inorganic-organic hybrid film.
[0086] [Table 2]
[0087] A phenyl-containing silica-based inorganic-organic hybrid film was formed on one side of each stainless steel foil produced using a die coater with a film thickness of 0.3, 3.0, or 5.0 μm. The drying oven was set to a furnace length of 3 m and a furnace temperature of 100°C, and the foil was transported at a speed of 5 mpm and wound up with a slightly adhesive protective film of PAC3J-30H attached. Next, while peeling off the protective film, the foil was passed through a hot air drying oven with a furnace length of 6 m and a furnace temperature of 400°C in a nitrogen atmosphere at a transport speed of 1 mpm, and wound up with a slightly adhesive protective film of PAC3J-30H attached to it, to obtain a stainless steel foil roll with a flattened film. 29Si-NMR confirmed that all Si nuclei were T nuclei. FTIR confirmed that the organic group was a phenyl group.
[0088] A coating solution for forming a methyl-group-containing silica-based organic-inorganic hybrid film was prepared by hydrolyzing and condensing 0.5 mol of methyltriethoxysilane and 0.5 mol of tetramethoxysilane in 6.0 mol of 2-ethoxyethanol with 2.0 mol of water and 0.1 mol of acetic acid, and then adding 6.0 mol of MEK and mixing.
[0089] A methyl-group-containing silica-based inorganic-organic hybrid film was formed on one side of each stainless steel foil produced using a die coater with a film thickness of 1.0 μm. The drying furnace was set to a furnace length of 3 m and a furnace temperature of 150 ° C., and the foil was transported at a speed of 5 mpm and wound up with a slightly adhesive protective film of PAC3J-30H attached. Next, while peeling off the protective film, the foil was passed through a hot air drying furnace in a nitrogen atmosphere with a furnace length of 6 m and a furnace temperature of 420 ° C. at a transport speed of 1 mpm, and wound up with a slightly adhesive protective film of PAC3J-30H attached to it, to obtain a stainless steel foil roll with a flattened film. 29Si-NMR confirmed that the Si nuclei were 50% T nuclei and 50% Q nuclei. FTIR confirmed that the organic group was a methyl group.
[0090] The results of evaluation of inclusions, flatness, and insulation reliability of the stainless steel foils with planarizing film produced as described above are shown in Tables 3, 4, 5, 6, 7, and 8. Here, observation of inclusions was performed on the surface of the stainless steel foil on which the planarizing film was not formed, and flatness and insulation reliability were evaluated on the surface on which the planarizing film was formed (the area corresponding to the back side of the stainless steel foil surface on which the inclusion evaluation was performed).
[0091] An SEM (JSM-IT500HR manufactured by JEOL Ltd.) was used to observe inclusions on the surface of stainless steel foil that had no planarizing film formed. A correlation was observed between the number of inclusions observed on the surface of stainless steel foil that had no planarizing film formed and the number of leakage current measurement points on the surface that had the planarizing film formed. The SEM settings were as follows: Detector: Backscattered electron detector BED-C Magnification: 80x Acceleration voltage: 20.0 kV Working Distance (WD): 10.0mm ·Irradiation current: 80% In addition, the images obtained by SEM were used to detect inclusions using automatic inclusion analysis software (particle analysis mode of AZtec manufactured by Oxford), and the composition of the inclusions was analyzed using an EDS device (ULTIM MAX 65 manufactured by Oxford).
[0092] In the process of identifying inclusions using the automatic inclusion analysis software, first an SEM image is acquired to be used in the automatic inclusion analysis software. Next, the image acquired by SEM is identified as an inclusion if the automatic inclusion analysis software detects an inclusion with a circular equivalent diameter of 2.00 μm or more and if at least one of the elements Al, Mg, Si, Ca, Mn, or S is detected by EDS. Images that have been subjected to EDS analysis are combined in the software and output as a single image. At this time, the particle size and elemental composition of the inclusions identified by the automatic inclusion analysis software are also acquired. The evaluation area is 100 cm 2 The circle equivalent diameter was taken as the grain size of the inclusion. The composition of the inclusions was calculated by calculating the mass % of Al2O3 and MgO in terms of oxides for the inclusions identified by the automatic inclusion analysis software.
[0093] [100cm 2 per 1μA / mm 2 or more leakage current measurement points] A flattening film was formed on the surface of a stainless steel foil to prepare a test piece. The cross-sectional area of the film immersed in a liquid with a conductivity of 0.1 S / m to 100 S / m was 1 mm 2 More than 25mm 2 The following electrode was used as the upper electrode, the stainless steel foil was used as the lower electrode, and the surface of the test piece was scanned with the upper electrode. When 10 V was applied between the upper electrode and the lower electrode, the leakage current was 1 μA / mm 2 The number of locations where this was the case was counted.
[0094] [Flatness] The test piece, 1 μA / mm 2At the locations where the above leakage current was measured, cracks were generated in the planarizing film, and the cracks caused steps on the surface of the planarizing film, reducing the planarization. Leak current is 1μA / mm 2 The point where this is the case is 100cm 2 When there were fewer than 10 defects per square inch, the flatness was judged to be good (◯), and when there were 10 or more defects, the flatness was judged to be unsuitable (×). Since the number of defects significantly increases with 10 or more defects, less than 10 defects was judged to be good.
[0095] [Insulation reliability] 1μA / mm 2 When the leakage current measured at the location was 0 to less than 10 points, the insulation reliability was evaluated as good (◯), and when the leakage current measured at the location was 10 points or more, the insulation reliability was evaluated as unsatisfactory (×).
[0096] [Table 3]
[0097] [Table 4]
[0098] [Table 5]
[0099] [Table 6]
[0100] [Table 7]
[0101] [Table 8]
[0102] Test materials 1-1, 1-2, 1-3, 1-4, 1-5, 2-1, 2-2, 2-3, 2-4, and 2-5 have low Al2O3 contents of 28.5 mass% or less and MgO contents of 9.7 mass% or less. These low contents of Al2O3 and MgO, which are inclusions that are difficult to refine by rolling, resulted in a low number of inclusions with a circle equivalent diameter of more than 5 μm, of 8.8 pieces / cm. 2 Therefore, the distance can be kept as low as 100cm or less. 2 per 1μA / mm 2 The number of leakage current measurement points was 9.5 or less, which is small, and it is clear that the occurrence of cracks has been reduced. In addition, as the plate thickness becomes thinner, the inclusions become finer, and the mass percentage of Al2O3, the mass percentage of MgO, and the number of inclusions with a circle equivalent diameter of more than 5 μm decrease. 2 per 1μA / mm 2 It can be seen that the number of measurement points for the above leakage current is small.
[0103] The stainless steel foils of test materials 1-6 and 2-6 had rolling reduction rates of less than 20% in each pass, and the inclusions could not be refined. As a result, they contained a large amount of Al2O3 (43.1 mass% or more) and MgO (19.4 mass% or more), and the number of inclusions with a circular equivalent diameter of more than 5 μm was 30.7 pieces / cm. 2 Therefore, the number of 100 cm 2 per 1μA / mm 2 The number of measurement points for the above leakage current was 32 or more, which is high, and therefore it can be seen that a large number of cracks occurred. In addition, compared to test materials 1-6 and 2-6, test materials 1-1, 1-2, 1-3, 1-4, 1-5, 2-1, 2-2, 2-3, 2-4, and 2-5, which were produced by changing the rolling conditions, had a rolling reduction rate of 20% or more in each pass, and the inclusions were refined, with reduced Al2O3 mass percentage, reduced MgO mass percentage, and reduced number of inclusions with an equivalent circle diameter of more than 5 μm.
[0104] The stainless steel foils of test materials 3-1 and 4-1 contained high amounts of Al2O3 at 35.1 mass% or more and MgO at 11.3 mass% or more. The high amounts of Al2O3 and MgO, which are inclusions that are difficult to refine by rolling, resulted in the number of inclusions with a circular equivalent diameter of more than 5 μm being 23.4 pieces / cm. 2 Therefore, the number of people who have been in a 100cm 2 per 1μA / mm 2 The number of measurement points for the above leakage current was high, at 30.0 or more, which indicates that a large number of cracks occurred. As a result, it can be seen that the content of Al and Mg in test materials 1 and 2 can be suppressed, and there is no contamination of Al or Mg from the refractory material as in test materials 3 and 4, so that the amount of Al2O3 and MgO is reduced and the number of inclusions with a circle equivalent diameter of more than 5 μm is reduced.
Claims
1. The composition includes a stainless steel component, and the balance includes Fe and impurities. With respect to the total mass of inclusions with a grain size of 2.00 μm or more, 2 O 3 : 30% by mass or less, MgO: 10% by mass or less, Among the inclusions with a particle size of 2.00 μm or more, the number of inclusions with a particle size of more than 5.00 μm present on the surface is 20 pieces / cm 2 is as follows: A stainless steel foil having a sheet thickness of 5.0 μm or more and 100.0 μm or less, and A stainless steel foil with a planarizing film, the stainless steel foil having a planarizing film having a thickness of 0.3 μm or more and 5.0 μm or less on at least one side of the stainless steel foil.
2. The stainless steel foil comprises, in mass%, C: 0.150% or less, Si: 0.050-2.000%, Mn: 0.100-10.000%, P: 0.045% or less, S: 0.007% or less, Ni: 2.000-15.000%, Cr: 15.000-20.000%, N: 0.200% or less, Al: 0.030% or less, Mg: 0.0005% or less, 2. The stainless steel foil with a flattened film according to claim 1, which is an austenitic stainless steel foil having a composition containing Ca: 0.0005% or less, with the balance being Fe and impurities.
3. The stainless steel foil comprises, in mass%, C: 0.120% or less, Si: 0.050-2.000%, Mn: 0.100-1.250%, P: 0.040% or less, S: 0.030% or less, Cr: 15.000-20.000%, N: 0.025% or less, Al: 0.030% or less, Mg: 0.0005% or less, 2. The stainless steel foil with a planarizing film according to claim 1, which is a ferritic stainless steel foil containing 0.0005% or less of Ca, with the balance being Fe and impurities.
4. The stainless steel foil with a planarized film according to any one of claims 1 to 3, wherein the planarized film is a silica-based organic-inorganic hybrid film, and the Si nuclei constituting the organic-inorganic hybrid film contain only T nuclei and Q nuclei.
5. 5. The stainless steel foil with a planarizing film according to claim 4, wherein the planarizing film is a silica-based organic-inorganic hybrid film, and the ratio of Q nuclei to Si nuclei constituting the organic-inorganic hybrid film is 70% or less.
Citation Information
Patent Citations
Inorganic-organic hybrid film-coated stainless foil
JP2003247078A
Austenitic stainless steel sheet having excellent detergency, and method for producing the same
JP2011202253A
Coating liquid for forming leveling film, and metal foil coil provided with leveling film
WO2016076399A1